Pembentukan Literasi Digital Gen Z Berbasis Nilai Kearifan Lokal dalam Membendung Konten Propaganda Terorisme Siber - Hidayat, Cecep; Effendi, Irmawan; Zarkasyi, Fajar Imam (CIC Lembaga Riset dan Konsultan Sosial, 2025)
This study aims to analyze the role of digital literacy among Generation Z based on local wisdom values, in countering cyber terrorism propaganda content. As an active internet-using demographic, Gen Z is particularly vulnerable to exposure to radical content due to a lack of information filtering skills. Using a qualitative approach, the study reveals that local cultural values embedded in the “Jabar Masagi” program—such as Niti Surti, Niti Harti, Niti Bukti, and Niti Bakti—has a potential modality to enhance Gen Z especially high junior students’ ability to evaluate and filter information, ultimately preventing the spread of cyber terrorism propaganda. These findings highlight the importance of integrating local wisdom values into digital literacy programs as a preventative measure against online radicalization, as well as the need for collaboration among various actors (government, educational institutions, and communities) in developing holistic digital literacy strategies.